The Concept of Justice in Buddhism: A Case Study of Caṇḍāla in Jātakaṭṭhakathā - Ratchatakorntrakoon, Ratchaneekorn; Chongstitvatana, Suchitra (International Journal of Engineering and Technology, 2018)
This article aims to study the function of Caṇḍāla, the outer caste character in Jātakaṭṭhakathā, the stories of the prior lives of the Buddha, and to study the relationship between the Caṇḍāla characters and the concept of justice in these Jātaka stories. In order to construct the concept of justice in Buddhism, and the framework of this study, Rawls’ theory regarding justice as fairness is used as a guideline for exploration of the Sutta, the Buddhist canon. The study reveals that the Caṇḍāla characters appear in nine Jātakas, playing significant roles in parts of many the prose narratives and the connection part of the story in order to illustrate that a low caste person can attain enlightenment. Three concepts of Dharma are conveyed by the Caṇḍāla characters in Jātakaṭṭhakathā: firstly, defilement causes humans in every caste to have suffering; secondly, every occurrence in one’s life depends on karma; and thirdly, humans in every caste have the potential to accomplish wisdom by understanding the path to eradicate suffering.
Keywords: Justice in Buddhism; Caá¹‡á¸Äla the outer caste; JÄtakaá¹á¹hakathÄ